MİDE KARSİNOMU OLGULARINDA KÜRATİF REZEKSİYONUN ERKEN VE GEÇ SONUÇLARI - ERSAN, Yılmaz; ERTÜRK, Süphan; ÇİÇEK, Yusuf; TEMİZ, Muhyittin; Doğusoy, Gülen; DİRİCAN, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background.- Despite recent advances in diagnosis and treatment, gastric carcinoma is still among the major causes of death in malignant diseases worldwide. The results of patients, whose underwent curative gastrectomy for gastric cancer at Cerrahpaşa Medical Faculty Department of General Surgery from 1989 to 1993, were analyzed, retrospectively. Design.- Clinical characteristics were retrieved from the records of patients who underwent curative gastrectomy for gastric cancer. Pathologic characteristics were determined from a detailed review of all available histopathologic slides and reports. Results.- One hundred fifty-four patients underwent curative resection during the study period in Cerrahpaşa Medical Faculty Department of General Surgery. Overall 5-year survival rate was 58%. The relationship between clinicopathologic variables and 5-year survival rate was evaluated by univariate and multivariate analysis. When a multivariate analysis with logistic regression of 5-year survival was performed, stage, grade, vascular/lymphatic/perineural invasion, depth of tumor invasion, levels of metastatic nodes and number of metastatic nodes emerged as the statistically significant in cases of curative resection. Conclusion.- These results suggest that the most important role for clinicians treating gastric carcinoma should be early diagnosis and aggressive surgery, followed by detailed pathologic examination.